Leveraging Network Effects for Global Customer Platform Development - Tuukkanen, Jaakko (My University, 2025)
Digital transformation is disrupting and reshaping processes, products and services in the Testing, Inspection and Certification (TIC) service ecosystem. The digital transformation drives the development of innovative technologies, including platforms that enhance connectivity among diverse stakeholders. The purpose of this master’s thesis was to understand the mechanisms of growth in digital B2B platforms. In the context of digital B2B platforms in TIC industry, this thesis identified what mechanisms underpin the network effects that escalate platform growth, and which strategies can amplify the network effect to benefit platform and its users. The first question was approached by literature review and the latter in a work-shop which was held as part of strategy formation process. Scenario-based roadmapping method was used to collect data to support the strategy formation and to validate how applicable existing research is for the context. Literature identifies ecosystem orchestration, trust mechanisms and value co-creation as growth mechanisms of digital B2B platforms. The strategic scenarios included establishment of strategic partnerships, leveraging AI capabilities and streamlining user experience to create value. Key findings of the research included identification of growth mechanisms applicable for the case company. An interesting finding was that neither the literature stream nor the outcome of strategy works considered the element of how to maintain growth. Even by applying all identified growth mechanisms, it is possible to accelerate growth, but the gap between scaling and maintaining remains for the future.
Keywords: network effect; platform economy; innovaatiot; digitalisaatio; strategiat; strateginen suunnittelu; strategy work; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management